Christian responses to Islam in Nigeria a contextual study of ambivalent encounters - Akinade, Akintunde E. (Christianities of the world, 2014)
In a world that is enveloped by skepticism, nihilism, provincialism, and mutual suspicion, a project on interreligious encounters opens new vistas of opportunities for thinking about creative ways to live together in our global village. Our world cries out for a new vision that will engender love, tolerance, peace, and justice. It is a vision that is sustained by deep faith in the goodness of our enduring religious traditions and a robust hope in humanity. Through a process of creative dialogue, we can begin to create new paradigms that will foster peace, reconciliation, and understanding. Christian Responses to Islam in Nigeria investigates the complex networks of competition, conflict, and cooperation in interreligious encounters in Nigeria. It studies how both contextual methods and holistic engagement can clarify and untangle some of the intricate conundrums that are discernible in the various ways Christians have responded to Islam in Nigeria. These two religious traditions are well represented in NIgeria. In fact, because of its demographic representation and balance, Nigeria presents a compelling case study for understanding emerging paradigms in interreligious encounters in Africa.